Experience with the Rapid Interactive Test for Autism in Toddlers in an Autism Spectrum Disorder Diagnostic Clinic. Issue 2 (February 2020) - Lemay, Jean-François; Amin, Parthiv; Langenberger, Shauna; McLeod, Scott
ABSTRACT: Objective: To examine the psychometric properties of the Rapid Interactive Screening Test for Autism in Toddlers (RITA-T) in an autism spectrum disorder (ASD) clinic for children aged 18 to 36 months. Methods: The RITA-T (level 2 screening instrument) was integrated into an ASD screening and diagnostic process for evaluating children aged 18 to 36 months who were referred to a pediatric tertiary care center. Scoring of the RITA-T to differentiate ASD from non-ASD developmental concerns was evaluated. Screening instrument measurements included sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), and negative likelihood ratio (LR−). Results: From a total of 239 participants aged 18 to 36 months (males = 78% and females = 22%), 201 (84%) were diagnosed with ASD (4:1 male-to-female ratio). An ASD diagnosis was significantly associated with RITA-T scores, with ASD patients scoring higher than non-ASD patients [F (1, 235) = 170, mean difference: males 9.21, mean difference: females 12.4, p < 0.001]. The RITA-T score was not statistically correlated with age or sex. The optimal cutoff score of ≥14 was determined from a receiver operator curve analysis (area under the curve = 0.953). In the study group, with a cutoff score of ≥14, the RITA-T showed a sensitivity of 0.97, specificity of 0.71, PPV of 0.95, NPV of 0.79, LR+ of 3.33, and LR− of 0.05. Conclusion: The RITA-T, as a level 2 screening instrument for ASD, exhibits discriminative psychometric properties similar to previously published results. When integrated into an ASD screening and diagnostic process for families for whom concerns about ASD have been raised with their children aged 18 to 36 months, the RITA-T helps to predict a best-estimate clinical diagnosis of ASD.